2017
DOI: 10.3847/1538-4357/aa901a
|View full text |Cite
|
Sign up to set email alerts
|

A Rogues’ Gallery of Andromeda's Dwarf Galaxies. I. A Predominance of Red Horizontal Branches

Abstract: We present homogeneous, sub-horizontal branch photometry of 20 dwarf spheroidal satellite galaxies of M31 observed with the Hubble Space Telescope. Combining our new data for 16 systems with archival data in the same filters for another four, we show that Andromeda dwarf spheroidal galaxies favor strikingly red horizontal branches or red clumps down to ∼10 4.2 L e (M V ∼−5.8). The age-sensitivity of horizontal branch stars implies that a large fraction of the M31 dwarf galaxies have extended star formation h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 76 publications
5
31
0
Order By: Relevance
“…We take the presence of a slope in our lower-mass galaxies as further evidence of an extended SFH in these galaxies, as also evidenced by the presence of red HB stars in the CMDs. In particular, And XIV is interesting because it hosts a more balanced (i.e., a more equal number of red HB and blue HB stars) HB (Martin et al 2017) in comparison to the other dSphs in the low-mass regime. From our spectroscopic abundance measurements, we find that it is more metal-poor than one would naively expect following the mass-metallicity relation (MZR, Section 7.3).…”
Section: Sfh Of M31 Dsphs From Coadded Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…We take the presence of a slope in our lower-mass galaxies as further evidence of an extended SFH in these galaxies, as also evidenced by the presence of red HB stars in the CMDs. In particular, And XIV is interesting because it hosts a more balanced (i.e., a more equal number of red HB and blue HB stars) HB (Martin et al 2017) in comparison to the other dSphs in the low-mass regime. From our spectroscopic abundance measurements, we find that it is more metal-poor than one would naively expect following the mass-metallicity relation (MZR, Section 7.3).…”
Section: Sfh Of M31 Dsphs From Coadded Spectramentioning
confidence: 99%
“…We also find tentative evidence for a slope in the [α/Fe]-[Fe/H] distribution for And IX (m = −0.12 ± 0.26). Using HST photometry, Martin et al (2017) found And IX was relatively metal-rich for its stellar mass, but they noted that their sample likely had some contamination from the M31 halo. Such contamination would flatten the slope.…”
Section: Sfh Of M31 Dsphs From Coadded Spectramentioning
confidence: 99%
“…Counts of faint galaxies detected 7 This assumes that the truncation in the ultrafaint dwarf SFH is set by reionization feedback effects. Recent observations of M31 ultrafaint dwarf galaxies have found extended SFHs, implying that the Milky Way utlrafaint satellite SFHs could be a product of local environmental effects such as non-uniform patchy reionization or stripping by the host (Martin et al 2017). in future imaging and HI surveys are therefore likely to provide strong constraints on WDM models.…”
Section: Predicted Galaxy Populations In Wdmmentioning
confidence: 99%
“…Even so, the information that we can extract from these few nearby E-mail: A.savino@rug.nl dwarf galaxies is very valuable and complements what we can learn from the study of unresolved, more distant galaxies (e.g., Gallazzi et al 2008;Boylan-Kolchin et al 2016;Goddard et al 2017). Moving beyond the satellites of the Milky Way, detecting the main sequence of the old population becomes challenging, and photometric data is often only able to reach down to the upper red giant branch (RGB) and the horizontal branch (HB) of galaxies (e.g., Martin et al 2016Martin et al , 2017.…”
Section: Introductionmentioning
confidence: 96%